2021
DOI: 10.1186/s12902-021-00711-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of prevalence of diabetes complications in Brazilian and Mexican adults: a cross-sectional study

Abstract: Background Type 2 diabetes is more frequent in Latin American people than in non-Hispanic whites due to a combination of genetic and lifestyle risk factors. Brazil and Mexico are the most populous countries in Latin America. The present study aimed to compare the results of the National Health Survey “PNS” in Brazil and the National Survey Health and Nutrition “ENSANUT” in Mexico regarding the prevalence, complications and healthcare issues of diabetes in both countries. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
(16 reference statements)
0
6
0
Order By: Relevance
“…Whilst it is known that diabetes mellitus is influenced by a number of known risk factors (modifiable and non-modifiable), the influence and impact of these risk factors is likely to vary between countries. Previous research found that diabetes mellitus in Mexico is associated with higher age, lower education, public health system, living in an urban area, and higher BMI ( 4 , 6 , 7 ). Whilst we show some similarities with already known risk factors (older age and BMI), our study shows other risk factors that were significantly associated with diabetes mellitus, including sex difference (females), low education level and low physical activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whilst it is known that diabetes mellitus is influenced by a number of known risk factors (modifiable and non-modifiable), the influence and impact of these risk factors is likely to vary between countries. Previous research found that diabetes mellitus in Mexico is associated with higher age, lower education, public health system, living in an urban area, and higher BMI ( 4 , 6 , 7 ). Whilst we show some similarities with already known risk factors (older age and BMI), our study shows other risk factors that were significantly associated with diabetes mellitus, including sex difference (females), low education level and low physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous cross-sectional studies using Mexican national surveys indicate that the prevalence of diabetes mellitus is increasing: 7.5% in 2000 ( 4 ), 9.2% in 2012 ( 5 ), 13.7% in 2016 ( 6 ), 14.7% in 2018 ( 7 ), and 16.9% in 2021 ( 8 ). It is now estimated that one in two children will develop diabetes mellitus in the future due to weight and lack of physical activity unless public health policies change ( 9 ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…When compare with statistics of other countries, Pakistan is facing a higher prevalence of T2D. Brazillian and Mexico population has prevalence of 8.8% [ 33 ], much lower than Pakistan [ 28 , 31 ]. Type 2 diabetes and obesity have a significant relationship [ 34 , 35 ] as body mass index (BMI) and type 2 diabetes risk and severity correlate positively [ 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it can lead to an increased risk of complications which impact people's quality of life, their finances, and generate an economic burden for the health system. It is important to point out that T2D is prevalent in Latin Americans due to a combination of genetic and lifestyle risk factors [3]. For the specific case of Mexico, the annual cost generated by DM is 17 billion USD; it is also in the list of the top ten countries with undiagnosed diabetics, where 4.9 million people have DM and do not know it.…”
Section: Introductionmentioning
confidence: 99%